Generation of tetracycline-controllable CYP3A4-expressing Caco-2 cells by the piggyBac transposon system - Moe Ichikawa (Nature Portfolio, 2021)
Abstract Caco-2 cells are widely used as an in vitro intestinal epithelial cell model because they can form a monolayer and predict drug absorption with high accuracy. However, Caco-2 cells hardly express cytochrome P450 (CYP), a drug-metabolizing enzyme. It is known that CYP3A4 is the dominant drug-metabolizing enzyme in human small intestine. In this study, we generated CYP3A4-expressing Caco-2 (CYP3A4-Caco-2) cells and attempted to establish a model that can simultaneously evaluate drug absorption and metabolism. CYP3A4-Caco-2 cells were generated by piggyBac transposon vectors. A tetracycline-controllable CYP3A4 expression cassette (tet-on system) was stably transduced into Caco-2 cells, thus regulating the levels of CYP3A4 expression depending on the doxycycline concentration. The CYP3A4 expression levels in CYP3A4-Caco-2 cells cultured in the presence of doxycycline were similar to or higher than those of adult small intestine. The CYP3A4-Caco-2 cells had enough ability to metabolize midazolam, a substrate of CYP3A4. CYP3A4 overexpression had no negative effects on cell proliferation, barrier function, and P-glycoprotein activity in Caco-2 cells. Thus, we succeeded in establishing Caco-2 cells with CYP3A4 metabolizing activity comparable to in vivo human intestinal tissue. This cell line would be useful in pharmaceutical studies as a model that can simultaneously evaluate drug absorption and metabolism.